Exploring the Relationships Between Four Aging Ideals: A Bibliometric Study - Lin, Ka; Ning, Yumei; Mumtaz, Ayesha; Li, Hua (Frontiers in Public Health, 2022)
When examining research articles on the aging strategies, four ideals (i.e., successful aging, healthy aging, productive aging and active aging) could be explored by conducting bibliometric analyses. For the literature analysis, general information on the four aging ideals was understood through visualization analysis; the intellectual base and research hotspots were intuitively observed. CiteSpace was used as the method to conduct the co-occurrence analysis of keywords in order to obtain research trends and cutting-edge knowledge in the field of aging-related policies. Subsequently, the study revealed the nature of the link between these four aging ideals and disclosed the connection between their fundamental principles. The study ultimately enhanced the understanding of the diverse contexts that have impacted the way in which these ideals influence policy, which has caused dissimilar strategies for policy development. The study also extended the discussion of the definitions of and relationships between these four ideals with the goal of identifying new directions for aging-related practice and providing innovative insights and references for investigators.